Website Administrasi Dance Sanggar Senam Dengan Model FAST - Marini; Sarwindah; Yurindra; Kiswanto; Anthonia Julia Cancera (Unversitas Muhammadiyah Riau, 2022)
Modern dance or dance today, is developing very quickly along with the times. Modern Dance originated in Europe, in 1930. The United States became the center of Modern Dance for experimentation. Modern Dance has several types of movements such as: Break Dance, Hip - Hop Dance, Popping Dance, Locking Dance, Ballroom Dance, and Shuffle Dance. These types of dances are different but after being performed, they are almost the same. Although the movements created have no explanation when expressed, many people like the movement. Dance Dances which are trending among young people are much liked by the public. At the sportsman level, there is a big influence in Indonesia. One of the popular enthusiasts in the community such as Modern Dance. The problems that often occur in Modern Dance are many people, namely information about how the lack of promotion so that many people do not know information about Dance. So we need a website to create a Dance information system. The goal is to facilitate the promotion of dance information. In developing this Dance information system website, it is necessary to analyze and design a website using the UML concept, Database Design with MySql. The result to be achieved is to implement a Dance Information System Website